Microstructure Evolution of Lithium‐Ion Battery Separator under Compressive Loading: In Situ Experiments and Image‐Based Finite Simulations. Issue 6 (27th April 2022) - Ai, Shigang; Xiao, Mingming; Chen, Jian; Wang, Panding; Li, Na; He, Jianchao; Song, Wei-Li; Chen, Hao-Sen
Abstract : The separator is the weakest mechanical part of a lithium‐ion battery. The displacement load formed by the expansion of an electrode induces the microstructure evolution of the separator, such as decreasing porosity and increasing tortuosity, which affects its ability to transport Li + and degrades battery performance. Herein, an in situ mechanical loading device combined with focused ion beam–scanning electron microscopy (FIB–SEM) is designed to reveal the real microstructure evolution of a separator under displacement loading. An image‐based finite‐element model is tailored to investigate the microstructure evolution and its nonuniformities of the separator at different deformation levels. The quantitative relationship between the separator porosity and external displacement load is presented based on the experimental and simulation results. Herein, new insight into the degradation mechanisms of commercial lithium‐ion batteries is provided. Abstract : An in situ mechanical loading device combined with focused ion beam–scanning electron microscopy is designed to investigate the microstructure evolution of the separator. An image‐based finite‐element model is tailored to simulate the microstructure evolution of the separator. A quantitative relationship between the porosity and compressive strain is presented.